Crossing boundaries in L2 writing development: a study of first-year academic writing students - Motlhaka, Hlaviso Albert (My University, 2018)
The study investigated the influence of Sepedi language in English writing and examined the rhetorical patterns of both Sepedi and English writing. The purpose of the study was to investigate possible ways in which L2 writers are given opportunities for HE, premised upon inclusion and diversity in accommodating their L1 (Sepedi language) for creative self-expression and socialization in English academic writing. The study used mixed method approach with sequential explanatory design to quantitatively and qualitatively investigate the rhetorical practices of L2 writers with Sepedi language background and evaluated the effectiveness of a socioculturally based intervention programme. The population consisted of 84 first-year students in the age range of 18 to 30, registered for English Communication Skills (ECS 1541) module in the School of Human and Social Sciences who were randomly selected due to Sepedi as their first language. Non-probability and probability sampling procedures were used to generate the sample as well as purposive and convenient sampling due to the qualities respondents possess in terms of Sepedi as their home language. Data was collected through questionnaires, essays, both focus group and semi-structured interviews to gain different perspectives and draw attention to different factors that affect the first-year students’ rhetoric practices of academic writing in both English and Sepedi. Quantitative data was analyzed using the SPSS Software version 24 through descriptive statistics and inferential statistics. Qualitative data was analyzed using inductive thematic analysis to develop a framework of the underlying structure of experiences or processes that are evident in the raw data as L2 writers traverse from Sepedi to English academic writing. The results revealed that the use of Sepedi and English in academic writing created positive experiences in which multilinguals intermingle linguistic features to naturalize epistemic access and identity affirmation to develop ideas and produce text content and organization. Furthermore, the results of this study ignited and restored the L2 writers’ confidence on the true worth of the essential principles behind African ways of thinking to encourage critical thinking, pride in embracing their linguistic repertoires in Sepedi in facilitating L2 writing. This study recommends that teachers should create a learning environment which allows L2 writers to use different languages in their essays to lessen the impact of cultural barriers by raising students’ awareness of cross-cultural contrastive rhetoric and facilitating their academic writing in the target language. It also recommends that teachers should use sociocultural writing strategies to advocate knowledge as experimentally and socially based wherein students reflected and shared their experiences of writing in both languages.
Thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in Applied Language and Literacy Education Faculty of Humanities School of Education University of Witwatersrand, Johannesburg, South Africa July, 2018